Engagement patterns in the reporting of the Arab-Israeli conflict in Al Jazeera English and the Washington Post - Warshaga, Abdallah. Z. A; Ang, Pei Soo; Huan, Changpeng (Journal of Modern Languages, 2024)
This study examines the portrayal of the Arab-Israeli conflict in two international newspapers: Al Jazeera English (AJE) and The Washington Post (WP). It explores the dialogic engagement within appraisal patterns in news reporting in two key events of the Deal of the Century and the Great Marches of Return. A total of 230 news texts (117 from WP and 113 from AJE) were examined, revealing differing engagement strategies of endorsement, attestation, and acknowledgement. AJE often critiqued US’s bias and gave precedence to Arab opposition to the Israeli occupation and US policies. WP, on the other hand, framed the conflict in the light of the US’s interests, often overlooking Arab grievances. The language used in conflict reporting plays a crucial role, and journalists need to recognise how their emotional evaluation could either obstruct or promote pathways to peaceful resolutions.